2017
DOI: 10.22236/jer_vol2issue2pp66-83
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Corpus-aided Discovery Learning in English Grammar Pedagogy

Abstract: The present study presents the instructional procedures of the implementation of corpusaided discovery learning and the extent to which corpus-aided discovery learning can create motivating and successful English grammar learning environment for EFL (English as a Foreign Language) students. Corpora promotes inductive learning in terms of that students not only acquire grammar by language data, observation and self-discovery of rules, but also find it entertaining and exciting to make grammar rule generalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
3
6
0
Order By: Relevance
“…Even though some learners found that learning the grammar structures via corpus-informed activities was more difficult than learning with a traditional book and they needed help or guidance from the teacher, another experience-described by Yanto and Indra Nugraha (2017)-has underlined the pleasure of perceiving the language as not artificial but alive and up-to-date. Students found it entertaining and exciting to make grammar rule generalization on their own.…”
Section: Uses Of Corpora In Language Teaching and Learningmentioning
confidence: 99%
“…Even though some learners found that learning the grammar structures via corpus-informed activities was more difficult than learning with a traditional book and they needed help or guidance from the teacher, another experience-described by Yanto and Indra Nugraha (2017)-has underlined the pleasure of perceiving the language as not artificial but alive and up-to-date. Students found it entertaining and exciting to make grammar rule generalization on their own.…”
Section: Uses Of Corpora In Language Teaching and Learningmentioning
confidence: 99%
“…Furthermore, the students' direct use of corpus seems fascinating since they deal with technology (Gilquin & Granger, 2010). Although those studies exhibit a positive response towards corpus use, a conflicting result in Yanto & Nugraha (2017) show that some students perceived studying grammar using corpus materials as tedious and difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this is not widely done in Indonesian contexts. A study on Indonesian students' perception has been conducted, but it focuses on corpusinformed materials in grammar class (Yanto & Nugraha, 2017). This study, thus, aims at portraying English Education Department students' perception of corpus use for language teaching to map further the possibility of offering the course(s) on corpus use for ELT in the EFL context.…”
Section: Introductionmentioning
confidence: 99%
“…In linguistics, corpus studies have widely recognized for many branches (Baker, 2003;Biber, 2006;Ismail, Idrus, & Syed Sahuri, 2020;Kranich, 2010;Makamani & Mutasa, 2017;Moon, 2016;Motschenbacher, 2018;Staples et al, 2018;Wright & Brookes, 2019). Aside from linguistics, corpus can also be applied for language teaching field (Akıncı & Yıldız, 2017;Arellano, 2018;Astika, 2018;Kim, 2019;Kızıl & Savran, 2018;Lin, 2016;Phoocharoensil, 2017;Yanto & Nugraha, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%